CATCH AND SIZE OF BULLET AND FRIGATE TUNA CAUGHT BY USING DRIFTING GILLNET IN INDIAN OCEAN OF INDONESIA BASED AT CILACAP FISHING PORT - Agustinus Anung Widodo; Fayakun Satria (Indonesian Fisheries Research Journal, 2013)
Pelagic fishes such as bullet and frigate tuna in the Indian Ocean were caught in Indian Ocean of Indonesian jurisdiction using various fishing gears including, drifting gillnet and landed in various fishing port in along coastal of west Sumatera (Banda Aceh, Pariaman, Bungus/Padang and Painan) as well as south Java, Bali and Nusatenggara (Muarabaru/Jakarta, Pelabuhanratu, Cilacap, Kedonganan, Benoa). In Cilacap, tuna drifting gillnet fishery is fishing bullet and frigate tuna as by product. The current work describes the catch and size distribution of bullet tuna (Auxis rochei Risso, 1810) and frigate tuna (Auxis thazard Lacepède, 1800) caught by drifting gillnet based at Cilacap Fishing Port. Data and information obtained through catch monitoring, port sampling and landing report of Cilacap Fishing Port 2011 as well as from Capture Fisheries Statistics of Indonesia 2010. The catch estimation of bullet and frigate tuna on drifting gillnet fishery is about 3.220 and 47.346 tons respectively. The catch rate of drifting gillnets on the frigate tuna was 0.364 mt/trip in 2006 decreased to 0.054 mt/trip in 2011 (decreased average 17% per year). The catchrate of drifting gillnets on the bullet tuna was also decreased from 0.178 mt/trip in 2006 to 0.013 mt/ trip in 2011. The FL of bullet and frigate tuna ranged respectively between 16-39cm and 25-46cm. Both species were mostly caught by drifting gillnet in adult size condition.